Pemetaan Kawasan Potensi Rawan Longsor: Studi Kasus : Kab.Tanah Datar, Prov. Sumatera Barat - Arif Okta Pratama (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
Rapid development has caused changes in land use patterns, where built space increasingly dominates and pressures natural spaces to change function (Pribadi et al., 2006) explaining that changes in land use patterns result in fluctuations in the carrying capacity of land resources, giving rise to land disasters. landslide (landslide). Buol et al. (1980) and Darmawijaya (1990) explained that landslides are essentially caused by the inability of the soil to support the load above it because the soil has experienced degradation of its soil properties. The method used in this research uses a weighted scoring method. The results of the analysis of 5 parameters of potential landslide-prone areas in Tanah Datar Regency obtained 3 classifications of levels of vulnerability, namely high-level landslide-prone areas covering an area of ​​2032.6955 ha, moderate-level landslide-prone areas covering an area of ​​16174.395 ha and low-level landslide-prone areas covering an area of ​​6284 ha. ,6345 ha. The most extensive area prone to landslides with a high level is in North Lintau Buo District. The area prone to moderate landslides is most extensive in North Lintau Buo District. The most extensive low-level landslide-prone areas are in Sepuluh Koto District.